Effect of top cover material on productivity of solar distillation unit (Bangladesh Journal of Medical Physics, 2018)
This work was taken up to design a cost effective and simple domestic scale solar water distillation device for use in the coastal villages of Bangladesh where saline free drinking water is scarce. This study mainly looked at the feasibility of using stretched transparent PVC cover in solar distillation devices in lieu of traditionally used transparent glass sheet. To increase total evaporative surface area of the bottom of stills, those were covered with black cotton fabrics with extended fibers. For the same angle of inclination (130) of the transparent cover, the average amount of distilled water produced by the transparent PVC sheet covered still was about 42% of that collected from a glass sheet covered still. The reason behind this poor performance could be traced to the increased surface adhesion of condensed water droplets with the PVC cover, which essentially scattered sunrays away from the solar still. So the way to go is to find a suitable plastic sheet material that has reduced surface adhesion to water or to find a coating material that can reduce surface adhesion too. Unless this can be done, traditional glass covered solar distillation device still remains the cover material of choice.Bangladesh Journal of Medical Physics Vol.9 No.1 2016 11-16